Nasal Carriage Rate of Methicillin Resistant Staphylococcus aureus among Health Care Workers at a Tertiary Care Hospital in Kathmandu, Nepal - Khatri, Sabita; Pant, Narayan Dutt; Bhandari, Raju; Shrestha, Krishma Laxmi; Shrestha, Chandrika D.; Adhikari, Nabaraj; Poudel, Asia (Journal of Nepal Health Research Council, 2017)
Background: Methicillin-resistant Staphylococcus aureus is one of the most common causes of nosocomial infections. Due to its multidrug resistant nature; infections due to Methicillin-resistant Staphylococcus aureus are often very difficult to treat. Colonized health care workers are the important sources of Methicillin-resistant Staphylococcus aureus. The objectives of this study were to determine the nasal carriage rate of Methicillin-resistant Staphylococcus aureus among health care workers at Kathmandu Medical College and Teaching Hospital, Nepal and to assess their antimicrobial susceptibility patterns. Methods: A cross sectional study was conducted among 252 health care workers from July to November 2013. Mannitol salt agar was used to culture the nasal swabs. Antimicrobial susceptibility testing was performed by Kirby- Bauer disc diffusion technique following Clinical and Laboratory Standards Institute guidelines. Methicillin-resistant Staphylococcus aureus strains were confirmed by using cefoxitin disc and by determining the minimum inhibitory concentration of oxacillin by agar dilution method. Results: Of 252 healthcare workers, 46(18.3%) were positive for Staphylococcus aureus among which 19(41.3%) were Methicillin-resistant Staphylococcus aureus carriers. Overall rate of nasal carriage of Methicillin-resistant Staphylococcus aureus was 7.5% (19/252).The higher percentages of lab personnel were nasal carriers of S. aureus (31.6%) and Methicillin-resistant Staphylococcus aureus (10.5%).The percentages of nasal carriage of S. aureus (35.7%) and Methicillinresistant Staphylococcus aureus (14.3%) were highest in the health care workers from post operative department. Higher percentage of Methicillin-resistant Staphylococcus aureus were susceptible toward amikacin (100%) and vancomycin (100%) followed by cotrimoxazole (84.2%). Conclusions: High rates of nasal carriage of S. aureus and Methicillin-resistant Staphylococcus aureus were observed among the healthcare workers, which indicate the need of strict infection control measures to be followed to control the nosocomial infections.